2014
DOI: 10.1016/j.tube.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D levels after recovery from tuberculosis: Insights into pathogenesis

Abstract: Objective 25-hydroxyvitamin D [25(OH)D] levels after recovery from tuberculosis (TB) may reflect pre-morbid levels and therefore provide insight into pathogenesis. We assessed 25(OH)D levels after recovery from TB disease, and compared to levels in persons without TB disease. Methods Case-control study. Cases were persons who had recovered from culture-confirmed Mycobacterium tuberculosis disease. Controls were persons without TB disease. Total 25(OH)D was measured from stored plasma specimens using liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(34 reference statements)
1
9
0
4
Order By: Relevance
“…The common biosignature driving increased molecular perturbation in blood was composed by key mediators of anti-M. tuberculosis innate immune response, such as IL-1 β and TNF-α, as well as IL-4 [36,55]. Previous studies have also reported abnormal immune responses in individuals with prior EPTB, supporting our findings of long lasting changes in immune profile [42][43][44]. Importantly, our findings have multiple possible implications.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The common biosignature driving increased molecular perturbation in blood was composed by key mediators of anti-M. tuberculosis innate immune response, such as IL-1 β and TNF-α, as well as IL-4 [36,55]. Previous studies have also reported abnormal immune responses in individuals with prior EPTB, supporting our findings of long lasting changes in immune profile [42][43][44]. Importantly, our findings have multiple possible implications.…”
Section: Discussionsupporting
confidence: 86%
“…Studying plasma biomarkers in the context of TB may provide important insights into diagnosis, treatment efficacy and also disease pathogenesis [33]. Several prior studies have reported concentrations of cytokines, chemokines, acute phase proteins and lipid mediators in populations of pulmonary TB patients [30,[34][35][36][37][38][39][40][41], but less is known about extrapulmonary infection [42][43][44]. Here, we performed multiparametric analyses of plasma concentrations of several inflammatory cytokines, soluble cytokine receptors, receptor ligands, alongside with lipid mediators in a large set of active TB patients with pulmonary or extrapulmonary disease to characterize the systemic inflammatory profile of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity, increased levels of systemic inflammation, hypoxia, poor nutrition, and use of corticosteroids have been implicated as major contributing factors 33 . Vitamin D deficiency is a risk factor of active TB and a sustained risk factor for TB recurrence even after recovery from active TB infection 34 , 35 . Vitamin D deficiency and compensatory rise in PTH may influence the pathogenesis of increased osteoporosis risk in patients with TB.…”
Section: Discussionmentioning
confidence: 99%
“…[30] We found in a previous study that persons with treated TB had lower levels of 25-hydroxvitamin D compared to uninfected controls. [31] In our current study we found that persons with previous extrapulmonary TB had low but similar median serum levels of 25-hydroxyvitamin D (24.4 ng/mL; IQR 15.4, 39.5) compared to persons with previous pulmonary TB (19.9 ng/mL; IQR 16.4, 34.3), LTBI (22.9 ng/mL; IQR 13.8, 25.8), and uninfected TB contacts (18 ng/mL; IQR 10.9, 26.3) (Kruskal-Wallis p = 0.23). Vitamin D levels < 30 ng/mL were considered low according to standard commercial breakpoints (LabCorp).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, there was no significant difference in 25-hydroxyvitamin D levels in participants with previous extrapulmonary TB and the three control groups, though median levels were low in all groups. In previous work, we demonstrated that 25-hydroxyvitamin D levels after recovery from TB were lower than in controls without TB disease, after controlling for important confounders—suggesting that low 25-hydroxyvitamin D levels could have been present prior to TB disease, and therefore contributed to TB risk [31]. However, there were no significant differences between those with previous extrapulmonary vs. pulmonary TB, [31] consistent with findings from other studies of persons with active TB disease [15, 45].…”
Section: Discussionmentioning
confidence: 99%